2013
DOI: 10.1021/am404946v
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the in Vivo Efficacy of Doxorubicin Loaded Hyaluronan Nanoparticles

Abstract: Magnetic nanoparticles are attractive platforms for biomedical applications including diagnosis and treatment of diseases. We have shown previously that hyaluronan-coated superparamagnetic iron oxide nanoparticles (HA-SPION) enhanced the efficacy of the conjugated anticancer drug doxorubicin (DOX) in vitro against drug-sensitive and drug-resistant human ovarian cancer cells. In this manuscript, we report our findings on the efficacy of DOX loaded HA-SPION nanoparticles in vivo using subcutaneous and intraperit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…59,60 Besides, it was found that HA-NIR accumulated in the tumor region, indicating active targeting ability of HA in CD44 receptor overexpressing tumors. 61,62 HA-NIR was also found to be present in spleen and heart. To further investigate the differences in tumor accumulation between HAH-NIR and HAL-NIR at 48 h postinjection, the fluorescence intensity of isolated tumor ( Figure 6D) was analyzed by Living Image software.…”
mentioning
confidence: 88%
“…59,60 Besides, it was found that HA-NIR accumulated in the tumor region, indicating active targeting ability of HA in CD44 receptor overexpressing tumors. 61,62 HA-NIR was also found to be present in spleen and heart. To further investigate the differences in tumor accumulation between HAH-NIR and HAL-NIR at 48 h postinjection, the fluorescence intensity of isolated tumor ( Figure 6D) was analyzed by Living Image software.…”
mentioning
confidence: 88%
“…Furthermore, HA-based nanocarriers were investigated as drug vehicles for systemic targeting of CD44-overexpressed cancers [268, 269]. HA-coated superparamagnetic iron oxide nanoparticles conjugated anticancer drug doxorubicin was delivered at much higher levels and distributed wider in the tumor tissue than intravenously injected free doxorubicin, leading to significant reduction of tumor growth [270]. HA-Irinotecan was tested in a phase II trial to determine progression-free survival in 5-fluorouracil refractory patients with metastatic colorectal cancer [271].…”
Section: Ha As Therapeuticmentioning
confidence: 99%
“…44 DOX delivered by the HA-nanoparticle is much more potent than free DOX against ovarian cancer in vitro 44 and in vivo . 4547 As CD44 is overexpressed in ER-/PR-/Her-2- or Triple Negative Breast Cancer (TNBC) cell lines. 48 We became interested in investigating whether HA coated nanoparticles can be utilized to enhance the drug efficacy against CD44-expressing TNBC cancer cells such as MDA-MB-231.…”
Section: Introductionmentioning
confidence: 99%